Cryopreserved Mesenchymal Stromal Cells Are Susceptible to T‐Cell Mediated Apoptosis Which Is Partly Rescued by IFNγ Licensing. (4th July 2016) - Chinnadurai, Raghavan; Copland, Ian B.; Garcia, Marco A.; Petersen, Christopher T.; Lewis, Christopher N.; Waller, Edmund K.; Kirk, Allan D.; Galipeau, Jacques
Abstract: We have previously demonstrated that cryopreservation and thawing lead to altered Mesenchymal stromal cells (MSC) functionalities. Here, we further analyzed MSC's fitness post freeze‐thaw. We have observed that thawed MSC can suppress T‐cell proliferation when separated from them by transwell membrane and the effect is lost in a MSC:T‐cell coculture system. Unlike actively growing MSCs, thawed MSCs were lysed upon coculture with activated autologous Peripheral Blood Mononuclear Cells (PBMCs) and the lysing effect was further enhanced with allogeneic PBMCs. The use of DMSO‐free cryoprotectants or substitution of Human Serum Albumin (HSA) with human platelet lysate in freezing media and use of autophagy or caspase inhibitors did not prevent thaw defects. We tested the hypothesis that IFNγ prelicensing before cryobanking can enhance MSC fitness post thaw. Post thawing, IFNγ licensed MSCs inhibit T cell proliferation as well as fresh MSCs and this effect can be blocked by 1‐methyl Tryptophan, an Indoleamine 2, 3‐dioxygenase (IDO) inhibitor. In addition, IFNγ prelicensed thawed MSCs inhibit the degranulation of cytotoxic T cells while IFNγ unlicensed thawed MSCs failed to do so. However, IFNγ prelicensed thawed MSCs do not deploy lung tropism in vivo following intravenous injection as well as fresh MSCs suggesting that IFNγ prelicensing does not fully rescue thaw‐induced lung homing defect. We identified reversible and irreversible cryoinjury mechanisms that result in susceptibility to host T‐cell cytolysis and affect MSC's cell survival and tissue distribution. The susceptibility of MSC to negative effects of cryopreservation and the potential to mitigate the effects with IFNγ prelicensing may inform strategies to enhance the therapeutic efficacy of MSC in clinical use. Stem Cells 2016;34:2429–2442